2006
DOI: 10.1111/j.1467-6435.2006.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Foreign Investors Punish Democracy? Theory and Empirics, 1984–2001

Abstract: SUMMARY Some claim that when level of property rights protection is controlled, democracy lowers foreign direct investment (FDI) to developing countries (Li and Resnick 2003). We critically examine the theoretical claims of the pessimistic arguments and show that FDI responds to preferences of countries and that democracies have a clear preference for FDI given that the scarce factor – capital – will find it harder under democracy to seek rents by raising barriers to entry. On the other hand, labor (the abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 59 publications
1
103
1
1
Order By: Relevance
“…Studies in the past have used the ICRG classification of investment profile of host nations to examine the level and extent of how payments, repatriation of profits and expropriation or viability of contracts are affected (Bandyopadhyay et al, 2013;Jakobsen & & Soysa, 2006;Mohamed & Sidiropoulos, 2010). We hypothesized that investment profile of host nation is expected to favor the inflow of FDI despite the discouraging effect of political risk (H1).…”
Section: Investment Profilementioning
confidence: 99%
“…Studies in the past have used the ICRG classification of investment profile of host nations to examine the level and extent of how payments, repatriation of profits and expropriation or viability of contracts are affected (Bandyopadhyay et al, 2013;Jakobsen & & Soysa, 2006;Mohamed & Sidiropoulos, 2010). We hypothesized that investment profile of host nation is expected to favor the inflow of FDI despite the discouraging effect of political risk (H1).…”
Section: Investment Profilementioning
confidence: 99%
“…Practical difficulties of corruption aside, Li and Resnick (2003) present empirical results that seem to be consistent with the notion that the existence of democracy is a dissuading factor for foreign investors who prefer to engage with autocracies. However, in a follow-up study, Jakobsen and de Soysa (2006) demonstrated that Li and Resnick's findings are very sensitive to the sample selection and the choice of modeling approach.…”
Section: Introductionmentioning
confidence: 98%
“…Schneider and Frey (1985) presented a model, which linked FDI inflows to a binary variable for a leftist executive, but the relationship proved to be statistically insignificant. In a more recent examination, Jakobsen and de Soysa (2006) used a similar measure and found a strong positive influence, indicating that pro-labor governments may welcome FDI due to their potential to reduce unemployment. The current investigation employs a different classification of political ideology compared to that used in Schneider and Frey (1985) and Jakobsen and de Soysa (2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li and Resnick (2003) show that when the level of property rights protection is controlled for, democracy reduces FDI to developing countries. Jakobsen and Soysa (2006) examine the same question and find that such negative relationship between democracy and FDI is fully dependent on sample size and estimation methodology. Their results support a strong positive relationship between democracy and FDI in developing countries.…”
Section: Literaturementioning
confidence: 99%